In the “Dim” Light of Ethnicity. Poetry of Mari Gennady Sabantsev-Oyar - Aleksey A. Arzamazov (Polylinguality and Transcultural Practices)
The study discusses the artistic features of the poetic work of Gennady Oyar, who is one of the most prominent representatives of modern Mari literature. The poems included in the collection “Flashes of the Heart” are analyzed in the context of the realities of the formation and development of Mari literature, taking into account the stage-typological specificity of the Finno-Ugric literatures of Russia. The motive-figurative cluster of Gennady Oyar’s works is examined, and the conclusion is drawn that his creative statements are deeply philosophical, actualizing universal human themes. It has been established that the poet in his poems “misses” a number of promising strategies that are important from the point of view of the implementation of his own creative concept, so the folklore and mythological component, going back to the traditional beliefs of the Mari, is poorly represented in Oyar’s figurative and symbolic system. At the same time, it was revealed that Gennady Oyar in his poetry pays great attention to the process of returning the historical truth of the Mari, without which the truthful construction of ethno-humanitarian intellectual reality is impossible. The work examines ethnically relevant topics and characters (the fate of the native language, the national intelligentsia, the tragedy of the poet and actor Yyvan Kyrli). The quality of the literary translation of Gennady Oyar’s texts into Russian is assessed. It is emphasized that his work corresponds with the main trends in the development of Mari literature at the turn of the 20th - 21st centuries.